2013
DOI: 10.3892/etm.2013.1204
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated osteoblastic adhesion on a porous manganese-incorporated TiO2 coating prepared by plasma electrolytic oxidation

Abstract: This study was conducted to evaluate the bioactivity of manganese-incorporated TiO2 (Mn-TiO2) coating prepared on titanium (Ti) plate by plasma electrolytic oxidation (PEO) technique in Ca-, P- and Mn-containing electrolytes. The surface topography, phase and element compositions of the coatings were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive spectrometry (EDS), respectively. The adhesion of osteoblast-like MG63 cells onto Ti, TiO2 and Mn-TiO2 surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…When manganese is substituted into the HA lattice (MnHA) the MnHA has the attractive feature of improving cellular adhesion [20,21,22,23,24]. Manganese (Mn) is an essential trace metal found in all tissues and is required for normal amino acid, lipid, protein, and carbohydrate metabolism [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When manganese is substituted into the HA lattice (MnHA) the MnHA has the attractive feature of improving cellular adhesion [20,21,22,23,24]. Manganese (Mn) is an essential trace metal found in all tissues and is required for normal amino acid, lipid, protein, and carbohydrate metabolism [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In improving the bioactivity of a material it is critical for the material to support cell attachment and the extracellular matrix which contains bioactive factors to induce regeneration [ 19 ]. When manganese is substituted into the HA lattice (MnHA) the MnHA has the attractive feature of improving cellular adhesion [ 20 , 21 , 22 , 23 , 24 ]. Manganese (Mn) is an essential trace metal found in all tissues and is required for normal amino acid, lipid, protein, and carbohydrate metabolism [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…177 Earlier, Lüthen et al 178 and Park et al 179 observed no significant positive regulation of osteoblasts by Mn 2+ in vitro. However, a manganese coating constructed by Zhang et al 61 promoted osteoblast adhesion and demonstrated an enhanced osteogenic effect. They proposed that the mechanism involves Mn 2+ binding to integrin subunits β 1 and α 1 and the subsequent mediation of the ERK and focal adhesion kinase (FAK) signaling pathways by Mn 2+ .…”
Section: Manganese Ion (Mn 2+ )mentioning
confidence: 99%
“…The presence of biological elements in the PEO coating has been reported to improve the bioactivity, resulting in enhanced cell adhesion, proliferation and osteoblastic differentiation [269,270]. In addition, several studies on bioactive element-enriched PEO coatings observed that cell proliferation is rather on par with non-modified Ti and even inferior to that on tissue culture polystyrene (TCPS), because other osteogenesis processes such as cell differentiation (conversion of one type of cells into a more specialized one), including collagen generation (building matrix of the bone), are facilitated instead [257,[271][272][273][274]. In those cases, surface microenvironment features trigger genetic pathways of cell differentiation (with specialized matrix synthesis) instead of the onset of mitosis and subsequent cell proliferation.…”
Section: Peo Of Ti Alloysmentioning
confidence: 99%